Students’ Motivation in Learning English Through AI-Based Learning - Theodora Evita Bella Lumban Raja; Dumaris E. Silalahi (Sean Institute, 2025)
This literature review investigates the influence of Artificial Intelligence (AI)-based English learning applications on learners’ motivation and engagement in English as a Foreign Language (EFL) contexts. The rapid growth of digital education has brought AI technologies such as Duolingo, ELSA Speak, Memrise, and ChatGPT-based tutors into language classrooms, transforming traditional pedagogy. Through a synthesis of recent empirical studies, this review explores how AI-based tools enhance motivation through adaptive feedback, gamification, personalization, and real-time support. It also identifies challenges such as the novelty effect, limited social interaction, and technological inequality. The findings indicate that AI platforms can boost intrinsic and extrinsic motivation by supporting autonomy, competence, and relatedness—core components of Self-Determination Theory (Deci & Ryan, 2000). Sustained motivation, however, requires integration with teacher guidance and social collaboration. AI tools serve best as complementary instruments that, when aligned with human empathy and pedagogy, foster engaging and sustainable learning experiences.